Physiological and perceptual responses of youth soccer players to an intensified period of competition - Patrick C Maughan, P. C.; Swinton, P. A. (International Journal of Sports Science & Coaching, 2020)
Intensified periods of competition create large increase in physical workload and can expose soccer players to numerous playing styles. The purpose of the study was to investigate the response of youth soccer players to an intensified period of competition and assess whether initial fitness influenced outcomes. Elite males across two consecutive years (n1 = 18, n2 = 18) were assessed for lower body strength and high-intensity endurance. Objective and subjective measures of fatigue were collected throughout five-day international tournaments using countermovement jumps (CMJ), a perceptual wellness questionnaire and match GPS data. Mixed effects models quantified the effects of time and fitness on outcomes. In general, results were consistent across both years. No significant interaction effects were obtained between time and fitness variables for any outcome ( 24 = 6.5; p = .225). CMJ height and power remained consistent across both tournaments ( 24 = 5.3; p = .262). In contrast, significant ( 24 = 17.7; p < .003) effects of time were obtained for GPS data with metrics exhibiting U-shape patterns with values returning to initial levels during final games. Greater variation was obtained for perceptual wellness data; however, responses to general muscle soreness and stress levels showed consistent decreases across both years ( 24 = 12.7; p = .013). Practitioners should be aware that basic measures collected from CMJ and GPS data may not be sensitive to fatigue accrued in youth soccer players across intensified periods of competition. In contrast, simple perceptual measures including general muscle soreness and stress may be more sensitive and assist with implementation of active recovery or load management strategies.